Pengaruh Susu Kedelai dan Bubur Kacang Hijau terhadap Lingkar Pinggang Wanita Pascamenopause - Fendie K. Syailawan; Budiyanti Wiboworini; Lilik Retna Kartikasari (Media Kesehatan Masyarakat Indonesia, 2019)
Postmenopausal women are prone to obesity. Soy milk and mung bean porridge contain fiber andflavonoids which are beneficial as anti-obesity. This study aimed to analyze the effect of soy milk and mungbean porridge on waist circumference among postmenopausal women. This was an experimental study usingpre-posttest with the control group. The study was conducted for 4 weeks from December 2018 to January2019 in Serengan, Surakarta. Subjects were randomly divided into control group (n=10), soy milk (n=10) andcombination of soy milk and mung bean porridge (n=10). Soy milk and mung bean porridge provided were 240ml and 180 ml/day/person and given for 4 weeks, respectively. Data were then analyzed with paired t-test, oneway ANOVA and Bonferroni test. There were no significant differences in the nutritional status, occupation andeducation level of the three groups. There was a significant reduction in waist circumference in both the soymilk and combination group compared to the control group (p<0.05). The mean decrease in waist cirumferencewas -2.40±2.23 cm in the soy milk group and -5.30±3.20 cm in the combination group. Soy milk and mungbean porridge can be alternative therapies to reduce waist circumference among postmenopausal women.